Implementasi Sistem Informasi Ujian - Irma Irawati Ibrahim (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Examination is extremely critical in educational institutions as it is used as an indicator of student’s learning quality achievement. Usually, there are two types of exams – Mid-Term and Final exams.The exam process consists of 3 processes, namely exam preparation, the exam itself, and grading submission. The control process, confidentiality, and efficiency are the main focus in examination improvement. Therefore, to provide the best solution for any potential problems, the researcher comprehensively conducted interviews, field study, problem identification, and analysis. The researcher chooses the Plan-Do-Act-Check method to ensure the best solution. Finally, cost-benefit analysis was run to measure the success of the system implementation. There are two types of benefit, tangible and intangible. This project resulted in a new exam flow procedure, exam information system, and cost-benefit analysis.